Corrigendum to: Assessment of the degree of adherence of medical laboratories to KDIGO 2012 guideline for evaluation and management of CKD in Czechia and Slovakia - Šálek, Tomáš; Friedecký, Bedřich; Kratochvíla, Josef; Pelinková, Květa; Budina, Marek (Biochemia medica, 2019)
[This corrects the article DOI: 10.11613/BM.2019.030704.].